Alzheimer's disease protease-containing plasma extracellular vesicles transfer to the hippocampus via the choroid plexus - Lee, Jung Hyun; Ostalecki, Christian; Oberstein, Timo; Schierer, Stefan; Zinser, Elisabeth; Eberhardt, Martin; Blume, Katja; Plosnita, Bianca; Stich, Lena; Bruns, Heiko; Coras, Roland; Vera González, Julio; et al. (EBioMedicine, 2022)
Background: Plasma extracellular vesicles (pEV) can harbor a diverse array of factors including active proteases and the amyloid-precursor-protein (APP) cleavage product Aβ, involved in plaque formation in Alzheimer`s diseases (AD). A potential role of such vesicles in AD pathology is unexplored. Methods: In a case-control study of randomly selected patients with AD and other neurological diseases (n = 14), and healthy controls (n = 7), we systematically analyzed the content of pEV, using different assay systems. In addition, we determined their entry path into brain tissue, employing animal (mice) injection experiments with ex vivo generated EV that were similar to AD-pEV, followed by multi antigen analysis (MAA) of brain tissue (n = 4 per condition). The results were compared with an IHC staining of human brain tissue in a small cohort of AD patients (n = 3) and controls with no neurodegenerative diseases (n = 3). Findings: We show that pEV levels are considerably upregulated in AD patients. Besides numerous inflammatory effectors, AD-pEV contained α-, β- and γ-secretases, able to cleave APP in in target cells. In vitro generated EV with similar characteristics as AD-pEV accumulated in the choroid plexus (CP) of injected animals and reached primarily hippocampal neurons. Corroborating findings were made in human brain samples. An inhibitor of hyaluronic-acid-synthetase (HAS) blocked uploading of proteases and Hyaluronan onto EV in vitro and abolished CP targeting in animal injection experiments. Interpretation: We conclude that protease-containing pEV could be part of a communication axis between the periphery and the brain that could be become detrimental depending on pEV concentration and duration of target cell impact.
CRIS-Team Scopus Importer:2022-03-04
Keywords: Alzheimer's disease; APP; Aβ; BACE; Choroid plexus; Hippocampus; Hyaluronan; Hyaluronic acid synthetase; Plasma extracellular vesicles; Secretases

Amyloid-beta levels and cognitive trajectories in non-demented pTau181-positive subjects without amyloidopathy - Oberstein, Timo; Schmidt, Manuel; Florvaag, Anna; Haas, Anna-Lena; Siegmann, Eva-Maria; Olm, Pauline; Utz, Janine; Spitzer, Philipp; Dörfler, Arnd; Lewczuk, Piotr; Kornhuber, Johannes; Maler, Juan Manuel (Brain, 2022)
In a long-term observational study, Oberstein et al. find that the biomarker constellation of increased pTau181, A beta 40 and A beta 42 in CSF is not associated with dementia. Further investigation of this biomarker profile may provide insights into the circumstances under which A beta becomes pathological.
CRIS-Team WoS Importer:2022-09-30

Amyloidogenic amyloid-?-peptide variants induce microbial agglutination and exert antimicrobial activity - Spitzer, Philipp; Condic, Mateja; Herrmann, Martin; Oberstein, Timo; Scharin-Mehlmann, Marina; Gilbert, Daniel; Friedrich, Oliver; Groemer, Teja; Kornhuber, Johannes; Lang, Roland; Maler, Juan Manuel (Scientific Reports, 2016)
Amyloid-? (A?) peptides are the main components of the plaques found in the brains of patients with Alzheimer's disease. However, A? peptides are also detectable in secretory compartments and peripheral blood contains a complex mixture of more than 40 different modified and/or N- and C-terminally truncated A? peptides. Recently, anti-infective properties of A? peptides have been reported. Here, we investigated the interaction of A? peptides of different lengths with various bacterial strains and the yeast Candida albicans. The amyloidogenic peptides A?1-42, A?2-42, and A?3p-42 but not the non-amyloidogenic peptides A?1-40 and A?2-40 bound to microbial surfaces. As observed by immunocytochemistry, scanning electron microscopy and Gram staining, treatment of several bacterial strains and Candida albicans with A? peptide variants ending at position 42 (A?x-42) caused the formation of large agglutinates. These aggregates were not detected after incubation with A?x-40. Furthermore, A?x-42 exerted an antimicrobial activity on all tested pathogens, killing up to 80% of microorganisms within 6 h. A?1-40 only had a moderate antimicrobial activity against C. albicans. Agglutination of A?1-42 was accelerated in the presence of microorganisms. These data demonstrate that the amyloidogenic A?x-42 variants have antimicrobial activity and may therefore act as antimicrobial peptides in the immune system.
EVALuna2:7714

Analysis of Surface Levels of IL-1 Receptors and Macrophage Scavenger Receptor I in Peripheral Immune Cells of Patients With Alzheimer Disease - Spitzer, Philipp; Weinbeer, Johannes; Herrmann, Martin; Oberstein, Timo; Condic, Mateja; Lewczuk, Piotr; Kornhuber, Johannes; Maler, Juan Manuel (Journal of Geriatric Psychiatry and Neurology, 2019)
Increased concentrations of interleukin 1 (IL-1) in the cerebrospinal fluid and serum of patients with Alzheimer disease (AD) reduced phagocytic capacity point to an inflammatory activation of mononuclear phagocytes in AD. Interleukin 1 receptors (IL-1R) and the macrophage scavenger receptor I (MSRI) are important players in IL-1 signaling and phagocytosis. In 20 patients with AD and 17 controls, IL-1RI, IL-1RII, and MSRI were assessed on peripheral blood mononuclear cells by flow cytometry. IL-1β, soluble IL-1 receptors, and IL-1R antagonist (IL-1Ra) were measured by enzyme-linked immunosorbent assay. The fraction of IL-1RI+ monocytes was increased by 10% and the expression of MSRI was reduced by 12% in AD. A 3.6% increased fraction of IL-1RI+ lymphocytes was accompanied by a 6.1% reduced expression of IL-1RII. The IL-1RI on monocytes and lymphocytes discriminated patients with AD with an accuracy of 0.79 and 0.75, respectively. The IL-1Ra was elevated in AD. Changes in the expression of IL-1 receptors and MSRI on peripheral blood cells fit to the concept of a proinflammatory state of the peripheral immune system. However, the observed differences are not strong enough to suggest their application as biomarkers for AD.
CRIS-Team Scopus Importer:2019-05-03
Keywords: Alzheimer disease; biomarker; dementia; IL-1RI; MSRI; neurodegeneration; neuroinflammation

A Specific Reduction in Aβ1-42 vs. a Universal Loss of Aβ Peptides in CSF Differentiates Alzheimer's Disease From Meningitis and Multiple Sclerosis - Spitzer, Philipp; Lang, Roland; Oberstein, Timo; Lewczuk, Piotr; Ermann, Natalia; Huttner, Hagen; Masouris, Ilias; Kornhuber, Johannes; Koedel, Uwe; Maler, Juan M. (Frontiers in Aging Neuroscience, 2018)
A reduced concentration of Aβ1-42 in CSF is one of the established biomarkers of Alzheimer's disease. Reduced CSF concentrations of Aβ1-42 have also been shown in multiple sclerosis, viral encephalitis and bacterial meningitis. As neuroinflammation is one of the neuropathological hallmarks of Alzheimer's disease, an infectious origin of the disease has been proposed. According to this hypothesis, amyloid pathology is a consequence of a microbial infection and the resulting immune defense. Accordingly, changes in CSF levels of amyloid-β peptides should be similar in AD and inflammatory brain diseases. Aβ1-42 and Aβ1-40 levels were measured in cerebrospinal fluid by ELISA and Western blotting in 34 patients with bacterial meningitis (n = 9), multiple sclerosis (n = 5) or Alzheimer's disease (n = 9) and in suitable controls (n = 11). Reduced concentrations of Aβ1-42 were detected in patients with bacterial meningitis, multiple sclerosis and Alzheimer's disease. However, due to a concurrent reduction in Aβ1-40 in multiple sclerosis and meningitis patients, the ratio of Aβ1-42/Aβ1-40 was reduced only in the CSF of Alzheimer's disease patients. Urea-SDS-PAGE followed by Western blotting revealed that all Aβ peptide variants are reduced in bacterial meningitis, whereas in Alzheimer's disease, only Aβ1-42 is reduced. These results have two implications. First, they confirm the discriminatory diagnostic power of the Aβ1-42/Aβ1-40 ratio. Second, the differential pattern of Aβ peptide reductions suggests that the amyloid pathology in meningitis and multiple sclerosis differs from that in AD and does not support the notion of AD as an infection-triggered immunopathology.
EVALuna2:36428

Astrocytes and microglia but not neurons preferentially generate N-terminally truncated A? peptides - Oberstein, Timo; Spitzer, Philipp; Klafki, Hans-Wolfgang; Linning, Philipp; Neff, Florian; Knoelker, Hans-Joachim; Lewczuk, Piotr; Wiltfang, Jens; Kornhuber, Johannes; Maler, Juan Manuel (Neurobiology of Disease, 2015)
The neuropathological hallmarks of Alzheimer's disease include extracellular neuritic plaques and neurofibrillary tangles. The neuritic plaques contain ?-amyloid peptides (A? peptides) as the major proteinaceous constituent and are surrounded by activated microglia and astrocytes as well as dystrophic neurites. N-terminally truncated forms of A? peptides are highly prevalent in neuritic plaques, including A? 3-x beginning at Glu eventually modified to pyroglutamate (A? N3pE-x), A? 2-x, A? 4-x, and A? 5-x. The precise origin of the different N-terminally modified A? peptides currently remains unknown. To assess the contribution of specific cell types to the formation of different N-terminally truncated A? peptides, supernatants from serum-free primary cell cultures of chicken neurons, astrocytes, and microglia, as well as human astrocytes, were analyzed by A?-ELISA and one- and two-dimensional SDS-urea polyacrylamide gel electrophoresis followed by immunoblot analysis. To evaluate the contribution of ?- and ?-secretase to the generation of N-terminally modified A?, cultured astrocytes were treated with membrane-anchored "tripartite ?-secretase (BACE1) inhibitors" and the ?-secretase inhibitor DAPT. Neurons, astrocytes, and microglia each exhibited cell type-specific patterns of secreted A? peptides. Neurons predominantly secreted A? peptides that begin at Asp1, whereas those released from astrocytes and microglia included high proportions of N-terminally modified A? peptides, presumably including A? 2/3-x and 4/5-x. The inhibition of BACE1 reduced the amount of A? 1-x in cell culture supernatants but not the amount of A? 2-x.
EVALuna2:23718

CEREBROSPINAL FLUID BIOMARKERS FOR CEREBRAL AMYLOID ANGIOPATHY - Sembill, Jochen; Lusse, C.; Linnerbauer, Mathias; Sprügel, Maximilian; Mrochen, Anne; Knott, Michael; Hölter, Philip; Engelhorn, Tobias; Schmidt, M.; Dörfler, Arnd; Oberstein, Timo; Maler, Juan Manuel; et al. (INTERNATIONAL JOURNAL OF STROKE, 2022)
CRIS-Team WoS Importer:2022-11-18

Cerebrospinal fluid biomarkers for cerebral amyloid angiopathy - Sembill, Jochen; Lusse, Christoph; Linnerbauer, Mathias; Sprügel, Maximilian; Mrochen, Anne; Knott, Michael; Engelhorn, Tobias; Schmidt, Manuel; Dörfler, Arnd; Oberstein, Timo; Maler, Juan Manuel; Kornhuber, Johannes; et al. (Brain Communications, 2023)
Integrating cerebrospinal fluid-biomarkers into diagnostic workup of patients with sporadic cerebral amyloid angiopathy may support early and correct identification. We aimed to identify and validate clinical- and cerebrospinal fluid-biomarkers for in vivo diagnosis of cerebral amyloid angiopathy. This observational cohort study screened 2795 consecutive patients admitted for cognitive complaints to the academic departments of neurology and psychiatry over a 10-year period (2009–2018). We included 372 patients with available hemosiderin-sensitive MR imaging and cerebrospinal fluid-based neurochemical dementia diagnostics, i.e. Aβ40, Aβ42, t-tau, p-tau. We investigated the association of clinical- and cerebrospinal fluid-biomarkers with the MRI-based diagnosis of cerebral amyloid angiopathy, applying confounder-adjusted modelling, receiver operating characteristic and unsupervised cluster analyses. We identified 67 patients with cerebral amyloid angiopathy, 76 patients with Alzheimer’s disease, 75 patients with mild cognitive impairment due to Alzheimer’s disease, 76 patients with mild cognitive impairment with unlikely Alzheimer’s disease and 78 healthy controls. Patients with cerebral amyloid angiopathy showed a specific cerebrospinal fluid pattern: average concentration of Aß40 [13 792 pg/ml (10 081–18 063)] was decreased compared to all controls (P < 0.05); Aß42 [634 pg/ml (492–834)] was comparable to Alzheimer’s disease and mild cognitive impairment due to Alzheimer’s disease (P = 0.10, P = 0.93) but decreased compared to mild cognitive impairment and healthy controls (both P < 0.001); p-tau [67.3 pg/ml (42.9–91.9)] and t-tau [468 pg/ml (275–698)] were decreased compared to Alzheimer’s disease (P < 0.001, P = 0.001) and mild cognitive impairment due to Alzheimer’s disease (P = 0.001, P = 0.07), but elevated compared to mild cognitive impairment and healthy controls (both P < 0.001). Multivariate modelling validated independent clinical association of cerebral amyloid angiopathy with older age [odds-ratio: 1.06, 95% confidence interval (1.02–1.10), P < 0.01], prior lobar intracerebral haemorrhage [14.00 (2.64–74.19), P < 0.01], prior ischaemic stroke [3.36 (1.58–7.11), P < 0.01], transient focal neurologic episodes (TFNEs) [4.19 (1.06–16.64), P = 0.04] and gait disturbance [2.82 (1.11–7.15), P = 0.03]. For cerebrospinal fluid-biomarkers per 1 pg/ml, both lower Aß40 [0.9999 (0.9998–1.0000), P < 0.01] and lower Aß42 levels [0.9989 (0.9980–0.9998), P = 0.01] provided an independent association with cerebral amyloid angiopathy controlled for all aforementioned clinical confounders. Both amyloid biomarkers showed good discrimination for diagnosis of cerebral amyloid angiopathy among adjusted receiver operating characteristic analyses (area under the receiver operating characteristic curves, Aß40: 0.80 (0.73–0.86), P < 0.001; Aß42: 0.81 (0.75–0.88), P < 0.001). Unsupervised Euclidian clustering of all cerebrospinal fluid-biomarker-profiles resulted in distinct segregation of cerebral amyloid angiopathy patients from all controls. Together, we demonstrate that a distinctive set of cerebrospinal fluid-biomarkers effectively differentiate cerebral amyloid angiopathy patients from patients with Alzheimer’s disease, mild cognitive impairment with or without underlying Alzheimer’s disease, and healthy controls. Integrating our findings into a multiparametric approach may facilitate diagnosing cerebral amyloid angiopathy, and may aid clinical decision-making, but warrants future prospective validation.
CRIS-Team Scopus Importer:2023-07-21
Keywords: biomarker; cerebral amyloid angiopathy; cerebrospinal fluid; dementia; small vessel disease

Cerebrospinal Fluid of Patients With Alzheimer's Disease Contains Increased Percentages of Synaptophysin-Bearing Microvesicles - Utz, Janine; Berner, Judith; Munoz, Luis Enrique; Oberstein, Timo; Kornhuber, Johannes; Herrmann, Martin; Maler, Juan Manuel; Spitzer, Philipp (Frontiers in Aging Neuroscience, 2021)
Introduction In Alzheimer's disease, the severity of symptoms is linked to a loss of synaptic density and the spread of pathologically hyperphosphorylated tau. The established cerebrospinal fluid markers A beta, tau and phospho-tau reflect the histopathological hallmarks of Alzheimer's disease but do not indicate disease progression. Such markers are of special interest, especially for trials of disease modifying drugs. Microvesicles are produced by stressed cells and reflect part of the metabolism of their cells of origin. Therefore, we investigated microvesicles of neuronal origin in cerebrospinal fluid. Materials and Methods We used flow cytometry to analyze microvesicles carrying tau, phospho-tau-Thr181, phospho-tau-Ser202Thr205, synaptophysin, and SNAP-25 in the cerebrospinal fluid of 19 patients with Alzheimer's disease and 15 non-inflammatory neurological disease controls. Results The percentages of synaptophysin-bearing microvesicles were significantly higher in the cerebrospinal fluid of patients with Alzheimer's disease than in the CSF of non-inflammatory neurological disease controls. Tau, phospho-tau-Thr181, phospho-tau-Ser202Thr205, and SNAP-25 did not differ between the groups. The percentages of synaptophysin-bearing vesicles distinguished patients with Alzheimer's disease from the controls (AUC = 0.81). Conclusion The loss of synapses in Alzheimer's disease may be reflected by synaptophysin-bearing microvesicles in the cerebrospinal fluid. Future studies are needed to investigate the possibility of using these MVs as a marker to determine the activity of Alzheimer's disease.
CRIS-Team WoS Importer:2021-07-30

Comment by European Alzheimer's Disease Consortium (EADC) investigators on the negative recommendation of the CHMP on the marketing authorization of donanemab for early Alzheimer' s disease - Jessen, Frank; Arbizu, Javier; Boada, Mercé; Balasa, Mircea; Bennys, Karim; Boban, Marina; Bürger, Katharina; Chincarini, Andrea; Cagnin, Annachiara; De Deyn, Peter Paul; Düzel, Emrah; Engelborghs, Sebastiaan; et al. (The Journal of Prevention of Alzheimer's Disease, 2025)
CRIS-Team Scopus Importer:2025-09-05

Comparison of ERlangen Score with pTau/Aβ1-42 Ratio for Predicting Cognitive Decline and Conversion to Alzheimer’s Disease - Schwarz, Julian Alexander; Schulz, Pauline; Utz, Janine; Rudtke, Laura; Jablonowski, Johannes; Klement, Neele; Lewczuk, Piotr; Kornhuber, Johannes; Maler, Juan Manuel; Oberstein, Timo (Brain Sciences, 2025)
Background/Objectives: The ERlangen Score (ERS) and the pTau/Aβ1-42 ratio are dementia risk scores that use only surrogate markers of amyloid and tau pathology, whose performance has taken on added importance with the advent of anti-amyloid antibody therapies. Direct comparisons between the scores are limited, which is why the performance of the ERlangen Score (ERS) and the pTau/Aβ1-42 ratio in predicting cognitive decline and dementia risk were compared. Methods: Measurements of Aβ1-42, Aβ1-40, and pTau181 were conducted in cerebrospinal fluid samples using immunoassays. Linear mixed models and the area under the receiver operating characteristic curve (AUC, receiver operating characteristic = ROC) of 259 non-demented subjects were calculated. Results: The pTau/Aβ1-42 ratio correctly identified 55 out of 60 individuals with a positive Aβ1-42/Aβ1-40 ratio and pTau181 as having Alzheimer’s disease (AD), while the ERS correctly identified all of these individuals. The model using the ERS to predict cognitive trajectories (Akaike Information Criterion AIC = 2365) exhibited a marginally superior fit than the model using the pTau/Aβ1-42 ratio (AIC = 2371). There was no statistically significant difference in the AUC of the ERS (0.717) for dementia risk compared to the pTau/Aβ1-42 ratio (0.739), p = 0.179. However, when the Aβ1-42/Aβ1-40 ratio was not included in the ERS (AUC = 0.685), the pTau/Aβ1-42 score was found to be statistically significantly better, p = 0.007. Conclusions: The ERS showed an advantage in grouping, identifying all patients with a positive Aβ1-42/Aβ1-40 ratio and elevated pTau181 as having AD. The ERS and pTau/Aβ1-42 ratio were comparable in predicting dementia or cognitive decline. However, when the Aβ1-42/Aβ1-40 ratio is not available, the pTau/Aβ1-42 ratio should be preferred.
CRIS-Team Scopus Importer:2025-05-02
Keywords: area under the curve; cognitive decline; comparison; ERlangen Score; pTau/Aß1-42; risk of dementia

Depression and attempted suicide under pregabalin therapy - Kustermann, Andreas; Möbius, Cornelia; Oberstein, Timo; Mueller, Helge H.; Kornhuber, Johannes (Annals of General Psychiatry, 2014)
Originally developed for the treatment of epilepsy, pregabalin has become a compound with a wide spectrum of indications comprising anxiety disorders and chronic pain and is therefore largely prescribed. Thus, it is important for clinicians to be aware of rare, but serious adverse effects. The following report illustrates the case of a 20-year-old male with a severe depressive syndrome following pregabalin medication which even led to a suicide attempt.
EVALuna2:22329

Development and technical validation of an immunoassay for the detection of app669–711 (Aβ−3–40) in biological samples - Klafki, Hans W.; Rieper, Petra; Matzen, Anja; Zampar, Silvia; Wirths, Oliver; Vogelgsang, Jonathan; Osterloh, Dirk; Rohdenburg, Lara; Oberstein, Timo; Jahn, Olaf; Beyer, Isaak; Lachmann, Ingolf; et al. (International Journal of Molecular Sciences, 2020)
The ratio of amyloid precursor protein (APP)669–711 (Aβ−3–40)/Aβ1–42 in blood plasma was reported to represent a novel Alzheimer’s disease biomarker. Here, we describe the characterization of two antibodies against the N-terminus of Aβ−3–x and the development and “fit-for-purpose” technical validation of a sandwich immunoassay for the measurement of Aβ−3–40. Antibody selectivity was assessed by capillary isoelectric focusing immunoassay, Western blot analysis, and immunohistochemistry. The analytical validation addressed assay range, repeatability, specificity, between-run variability, impact of pre-analytical sample handling procedures, assay interference, and analytical spike recoveries. Blood plasma was analyzed after Aβ immunoprecipitation by a two-step immunoassay procedure. Both monoclonal antibodies detected Aβ−3–40 with no appreciable cross reactivity with Aβ1–40 or N-terminally truncated Aβ variants. However, the amyloid precursor protein was also recognized. The immunoassay showed high selectivity for Aβ−3–40 with a quantitative assay range of 22 pg/mL–7.5 ng/mL. Acceptable intermediate imprecision of the complete two-step immunoassay was reached after normalization. In a small clinical sample, the measured Aβ42/Aβ−3–40 and Aβ42/Aβ40 ratios were lower in patients with dementia of the Alzheimer’s type than in other dementias. In summary, the methodological groundwork for further optimization and future studies addressing the Aβ42/Aβ−3–40 ratio as a novel biomarker candidate for Alzheimer’s disease has been set.
CRIS-Team Scopus Importer:2020-09-18
Keywords: Alzheimer’s disease; Amyloid β; Assay development; Assay validation; Biomarker

Digit Ratio (2D:4D) Is Not Associated with Alzheimer’s Disease in the Elderly - Siegmann, Eva-Maria; Olm, Pauline; Lenz, Bernd; Mühle, Christiane; Oberstein, Timo; Maler, Juan Manuel; Kornhuber, Johannes (Brain Sciences, 2023)
The development of Alzheimer’s disease (AD) is influenced by sex hormones—estrogens and androgens in particular. However, the impact of prenatal sex hormone exposure is less clear; very few investigations have examined the relationship between the second-to-fourth digit length ratio (2D:4D), a putative proxy for the ratio of prenatal estrogens to androgens, and AD, with inconsistent results among the few that have. Therefore, we aimed to investigate this relationship using methodologically robust metrics. In a 2 (sex) × 4 (group) MANOVA incorporating 108 participants (30 AD patients, 19 patients with tauopathy but no amyloidopathy, 31 clinical and 28 healthy age- and education-matched controls), the effects of sex and group on the dependent variables right and left 2D:4D were examined. We also explored the association between 2D:4D and the severity of AD symptoms assessed via neuropsychological examination. We did not find any significant differences in the right- and left-hand 2D:4D between patients with AD and the other groups; no significant associations between 2D:4D and neuropsychological task performances were found in the dementia groups. The 2D:4D of healthy women was significantly lower than that of depressed women without AD, i.e., clinical controls, but not significantly different from depressed female patients with AD. This investigation does not support the role of 2D:4D in the development or severity of AD in general, but suggests a potential role of 2D:4D for depression in women. Future studies are warranted to clarify whether 2D:4D can distinguish between early- and late-onset depression in women.
CRIS-Team Scopus Importer:2023-10-06
Keywords: Alzheimer’s disease; dementia; digit ratio; fetal development; finger length ratio

Identification of a rare presenilin 1 single amino acid deletion mutation (F175del) with unusual amyloid-β processing effects - Vöglein, Jonathan; Willem, Michael; Trambauer, Johannes; Schönecker, Sonja; Dieterich, Marianne; Biskup, Saskia; Giudici, Camilla; Utz, Kathrin; Oberstein, Timo; Brendel, Matthias; Rominger, Axel; Danek, Adrian; et al. (Neurobiology of Aging, 2019)
We report the novel presenilin 1 (PSEN1) single amino acid deletion mutation F175del. Comprehensive clinical work-up, including cerebral MRI, FDG-PET, and CSF analysis, was performed in a male who had developed forgetfulness at the age of 39. Alzheimer's disease dementia was diagnosed according to established criteria. The index patient manifested rapid progressive dementia, seizures, and myoclonus, and a Pisa syndrome as a side effect of donepezil treatment. The PSEN1 mutation F175del was found on genetic testing. It was rendered very likely pathogenic as amyloid-β (Aβ) peptide 42 was elevated in a cell culture model compared to presenilin 1 wild-type controls. An additional, unusual increase in Aβ39 indicates a rarely observed product line deviation in the generation of the shorter Aβ species. Our observations extend the range of PSEN1 mutations to be considered in familial dementia. We demonstrate that deletion of a single conserved amino acid, which is very rare compared to missense mutations as the common cause for PSEN1-associated Alzheimer's disease, can lead to an unusual profile of Aβ species.
CRIS-Team Scopus Importer:2019-10-25
Keywords: Alzheimer's disease; Autosomal dominant; Genetics; Novel mutation; PSEN1

Imbalance of Circulating Th17 and Regulatory T Cells in Alzheimer's Disease: A Case Control Study - Oberstein, Timo; Taha, Lava; Spitzer, Philipp; Hellstern, Janina; Herrmann, Martin; Kornhuber, Johannes; Maler, Juan Manuel (Frontiers in Immunology, 2018)
The neuropathological hallmarks of Alzheimer's disease (AD), i.e., neuritic plaques and neurofibrillary tangles, consist of beta amyloid peptides (Aβ) and hyperphosphorylated Tau. These are accompanied by reactive microglia and astrocytes in the vicinity of the neuritic plaques and by changes to the peripheral immune system, e.g., an increase of the pro-inflammatory cytokines IL-1β, IL-6, and TNF-α in the peripheral blood. To address a potential involvement of peripheral T helper cell (Th) subsets in AD, we conducted a case control study with 54 individuals with AD dementia (n = 14), with mild cognitive impairment (MCI) due to AD (MCIAD, n = 14), with MCI unlikely due to AD (MCIother, n = 13), and controls without cognitive impairment (controls, n = 13). The proportions of CD3+CD8-IL-17A+IFNγ- Th17 cells, CD3+CD8-IL-17A-IFNγ+ Th1 cells, and CD4+CD127lowCD25+ regulatory T cells (Tregs) were assessed by flow cytometry. In addition, the correlations of the proportions of Th subsets to cerebrospinal fluid biomarkers were studied. CD3+CD8-IL-17A+IFNγ- Th17 cells were significantly increased in subjects with MCIAD compared to age- and sex-matched subjects with MCIother and controls (MCIAD mean = 1.13, SD = 0.77; MCIother mean = 0.58, SD = 0.28; and controls mean = 0.52, SD = 0.22; p = 0.008). The proportion of CD4+CD127lowCD25+ Tregs was not altered between the different groups, but it significantly positively related with the levels of total Tau and pTau181 (rTreg|totalTau = 0.43, p = 0.021, n = 28; rTreg|pTau181 = 0.46; p = 0.024, n = 28) in subjects with AD but not in nonAD controls (rTreg|totalTau = -0.51, p = 0.007, n = 26). The increase of circulating CD3+CD8-IL-17A+IFNγ- Th17 cells in the early stages of AD and the association of CD4+CD127lowCD25+ Tregs with neurodegeneration marker Tau may indicate that the adaptive immune system relates to neuropathological changes in AD.
EVALuna2:211630

Microvesicles from cerebrospinal fluid of patients with Alzheimer’s disease display reduced concentrations of tau and APP protein - Spitzer, Philipp; Mulzer, Linda-Marie; Oberstein, Timo; Munoz, Luis Enrique; Lewczuk, Piotr; Kornhuber, Johannes; Herrmann, Martin; Maler, Juan Manuel (Scientific Reports, 2019)
Microvesicles are small membranous particles generated during cellular activation or stress. The analysis of the content and the surface of microvesicles allow conclusions about the cells they are originating from and the underlying pathology. Therefore, CSF microvesicles have been suggested to be promising targets to monitor the (etio)pathology of neurodegenerative diseases. Microvesicles in the CSF of 15 patients with Alzheimer’s disease and 15 controls were analyzed by flow cytometry regarding the levels of CD3, CD4, CD45, CD64, BACE1, Aβ, APP and tau. The results were replicated in a second cohort comprising 14 patients with Alzheimer’s disease and 9 controls. The levels of tau and APP were reduced in microvesicles of Alzheimer’s disease patients. A significant change was neither observed in the number of microvesicles nor in the expression of the other antigens. Tau and APP in microvesicles separated patients with Alzheimer’s disease from controls with an AUC of 0.84 and 0.89 respectively. We conclude that tau and APP in CSF microvesicles are promising biomarkers which could directly provide information about the Alzheimer pathology on a cellular level.
CRIS-Team Scopus Importer:2019-05-21

Novel, standardized sample collection from the brain-nose interface - San Nicoló, Marion; Mertzig, Sabine; Berghaus, Alexander; Peters, Oliver; Frölich, Lutz; Grimmer, Timo; Wiltfang, Jens; Oberstein, Timo; Braun, Thomas; Babu, Maria; Wunderlich, Hilary; Kaspar, Peter; et al. (Methods, 2025)
Background: Diagnostics for neurodegenerative diseases lack non-invasive approaches suitable for early-stage biochemical screening and routine examination of neuropathology. Biomarkers of neurodegenerative diseases pass through the brain-nose interface (BNI) and accumulate in nasal secretion. Sample collection from the brain-nose interface presents a compelling prospect as basis for a non-invasive molecular diagnosis of neuropathologies. Here, we evaluated a novel medical device (nosecollect) that is tailored for the standardized collection of nasal secretion samples from BNI, focusing on its sample collection safety and efficiency. Method: A class I medical device (nosecollect) was developed, to enable the standardized collection of nasal secretion exclusively from BNI in a user-friendly, safe, and comfortable manner. We performed a clinical study to test the collection device on a heterogenous cohort (n = 923) at 8 study centers and evaluated its performance to collect sufficient sample volume from the targeted BNI area, its safety and tolerability. Samples were collected by trained medical personnel (medical doctors and nurses). Results: Nosecollect gathered a mean volume of 452 ± 317 μl from the BNI. Successful positioning of the absorption material (AM) in the BNI was observed in 95 % of the cases. Pain level/level of discomfort and occurrences of adverse events remained minimal (visual analogue scale (VAS) = 1.97 ± 1.99 (range 0–10), adverse events: 1 %, no serious adverse events). Analysis of the nasal secretion sample identified detectable levels of CNS biomarkers in it. Conclusions: The precision and ergonomic design of nosecollect ensures a standardized, targeted and safe collection of non-diluted nasal secretion samples from BNI, thus outperforming traditional methods such as swabs, lavage etc which are not customized for accessing undiluted samples from BNI. In addition, the device offers a non-invasive and accessible approach for the acquisition of nasal secretion samples from BNI, signifying a crucial step in the future development of a BNI-based non-invasive diagnostic platform for neurodegenerative diseases.
CRIS-Team Scopus Importer:2025-01-31
Keywords: Biomarkers; Cerebrospinal fluid; Nasal secretion; Neurodegenerative diseases; Non-invasive

N-truncated Aβ2-X starting with position two in sporadic Alzheimer's disease cases and two Alzheimer mouse models - Savastano, Adriana; Klafki, Hans; Haussman, Ute; Oberstein, Timo; Muller, Petr; Wirths, Oliver; Wiltfang, Jens; Bayer, Thomas A. (Journal of Alzheimer's Disease, 2016)
According to the modified amyloid hypothesis, the key event in the pathogenesis of Alzheimer's disease (AD) is the deposition of neurotoxic amyloid ?-peptides (A?s) in plaques and cerebral blood vessels. Additionally to full-length peptides, a great diversity of N-truncated A? variants is derived from the larger amyloid-? protein precursor (A?PP). Vast evidence suggests that A?x-42 isoforms play an important role in triggering neurodegeneration due to their high abundance, amyloidogenic propensity and toxicity. Although N-truncated A? peptides and A?x-42 species appear to be the crucial players in AD etiology, the A?2-X isoforms did not receive much attention yet. The present study is the first to show immunohistochemical evidence of A?2-X in cases of AD and its distribution in A?PP/PS1KI and 5XFAD transgenic mouse models using a novel antibody pAB77 that has been developed using A?2-14 as antigen. Positive plaques and congophilic amyloid angiopathy (CAA) were observed in AD cases and in both mouse models. While in AD cases, abundant CAA and less pronounced plaque pathology was evident, the two mouse models showed predominantly extracellular A? deposits and minor CAA staining. Western blotting and a capillary isoelectric focusing immunoassay demonstrated the high specificity of the antibody pAb77 against A?-variants starting with the N-terminal Alanine-2.
EVALuna2:23766

N-truncation and pyroglutaminylation enhances the opsonizing capacity of A?-peptides and facilitates phagocytosis by macrophages and microglia - Condic, Mateja; Oberstein, Timo; Herrmann, Martin; Reimann, Mareike Carola; Kornhuber, Johannes; Maier, Jan-Niklas; Spitzer, Philipp (Brain Behavior and Immunity, 2014)
Abnormal accumulations of amyloid-? (A?)-peptides are one of the pathological hallmarks of Alzheimer's disease (AD). The precursor of the A?-peptides, the amyloid precursor protein (APP), is also found in peripheral blood cells, but its function in these cells remains elusive. We previously observed that mononuclear phagocytes release A?-peptides during activation and phagocytosis, suggesting a physiologic role in inflammatory processes. Here, we show that supplementing the media with soluble N-terminally truncated A?(2-40) and A?(2-42) as well as A?(1-42) induced the phagocytosis of polystyrene particles (PSPs) by primary human monocytes. If the PSPs were pre-incubated with A?-peptides, phagocytosis was induced by all tested A?-peptide species. N-terminally truncated A?(x-42) induced the phagocytosis of PSPs significantly more effectively than did A?(x-40). Similarly, the phagocytosis of Escherichia coli by GM-CSF- and M-CSF-elicited macrophages as well as microglia was particularly facilitated by pre-incubation with N-terminally truncated A?(x-42). The proinflammatory polarization of monocytes was indicated by the reduced MSRI expression and IL-10 secretion after phagocytosis of PSPs coated with A?(1-42), A?(2-42) and A?(3p-42). Polarization of the macrophages by GM-CSF reduced the phagocytic activity, but it did not affect the capabilities of A?-peptides to opsonize prey. Taken together, A?-peptides support phagocytosis as soluble factors and act as opsonins. Differential effects among the A?-peptide variants point to distinct mechanisms of interaction among monocytes/macrophages, prey and A?-peptides. A proinflammatory polarization induced by the phagocytosis of A?-peptide coated particles may provide a model for the chronic inflammatory reaction and sustained plaque deposition in AD.
EVALuna2:13018

PASSED: Brain atrophy in non-demented individuals in a long-term longitudinal study from two independent cohorts - Haas, Anna-Lena; Olm, Pauline; Utz, Janine; Siegmann, Eva-Maria; Spitzer, Philipp; Florvaag, Anna; Schmidt, Manuel; Dörfler, Arnd; Lewczuk, Piotr; Kornhuber, Johannes; Maler, Juan Manuel; Oberstein, Timo (Frontiers in Aging Neuroscience, 2023)
Introduction: Alzheimer’s disease (AD) is indicated by a decrease in amyloid beta 42 (Aβ42) level or the Aβ42/Aβ40 ratio, and by increased levels of Tau with phosphorylated threonine at position 181 (pTau181) in cerebrospinal fluid (CSF) years before the onset of clinical symptoms. However, once only pTau181 is increased, cognitive decline in individuals with subjective or mild cognitive impairment is slowed compared to individuals with AD. Instead of a decrease in Aβ42 levels, an increase in Aβ42 was observed in these individuals, leading to the proposal to refer to them as nondemented subjects with increased pTau-levels and Aβ surge with subtle cognitive deterioration (PASSED). In this study, we determined the longitudinal atrophy rates of AD, PASSED, and Biomarker-negative nondemented individuals of two independent cohorts to determine whether these groups can be distinguished by their longitudinal atrophy patterns or rates. Methods: Depending on their CSF-levels of pTau 181 (T), total Tau (tTau, N), Aβ42 or ratio of Aβ42/Aβ40 (A), 185 non-demented subjects from the Alzheimer’s Disease Neuroimaging Initiative (ADNI) and 62 non-demented subjects from Erlangen AD cohort were assigned to an ATN group (A–T–N–, A–T+N±, A+T–N±and A+T+N±) and underwent T1-weighted structural magnetic resonance imaging (sMRI). Longitudinal grey matter (GM) atrophy patterns were assessed with voxel-based morphometry (VBM) using the cat12 toolbox on spm12 (statistical parametric mapping) of MRI scans from individuals in the ADNI cohort with a mean follow-up of 2 and 5 years, respectively. The annualized atrophy rate for individuals in the Erlangen cohort was determined using region of interest analysis (ROI) in terms of a confirmatory analysis. Results: In the A–T+N± group, VBM did not identify any brain region that showed greater longitudinal atrophy than the A+T+N±, A+T+N± or biomarker negative control group. In contrast, marked longitudinal atrophy in the temporal lobe was evident in the A+T–N± group compared with A+T–N± and biomarker-negative subjects. The ROI in the angular gyrus identified by VBM analysis of the ADNI cohort did not discriminate better than the hippocampal volume and atrophy rate between AD and PASSED in the confirmatory analysis. Discussion: In this study, nondemented subjects with PASSED did not show a unique longitudinal atrophy pattern in comparison to nondemented subjects with AD. The nonsignificant atrophy rate compared with controls suggests that increased pTau181-levels without concomitant amyloidopathy did not indicate a neurodegenerative disorder.
CRIS-Team Scopus Importer:2023-03-24
Keywords: Alzheimer disease/physiopathology*; amyloid beta-peptides/cerebrospinal fluid*; ATN classification; longitudinal studies; magnetic resonance imaging; medial temporal lobe; SNAP; tau proteins/cerebrospinal fluid*

Pharmacological Inhibition of Amyloidogenic APP Processing and Knock-Down of APP in Primary Human Macrophages Impairs the Secretion of Cytokines - Spitzer, Philipp; Walter, Matthias; Göth, Caroline; Oberstein, Timo; Linning, Philipp; Knölker, Hans Joachim; Kornhuber, Johannes; Maler, Juan Manuel (Frontiers in Immunology, 2020)
It has been previously shown that the amyloid precursor protein (APP) support the innate immune defense as an immune receptor. Amyloid β (Aβ) peptides seem to have properties of an antimicrobial peptide and can act as opsonines. In APP-deficient mouse models, a reduced secretion of cytokines has been observed. Still, it is unclear whether this can be attributed to the lack of APP or to the missing secretion of Aβ peptides. We inhibited the secretion of Aβ peptides in primary human monocyte derived macrophages with the γ-secretase inhibitor N-[N-(3,5-Difluorophenacetyl)-L-alanyl]-S-phenylglycine-t-butyl-ester (DAPT) or the β-secretase inhibitor GL-189. Alternatively, we knocked down APP by transfection with siRNA. We measured tumor necrosis factor α (TNFα), interleukin 6 (IL-6) and interleukin (IL-10) by enzyme linked immunosorbent assay (ELISA) and evaluated the phagocytotic activity by flow cytometry. We observed reduced concentrations of TNFα and IL-6 in the media of APPk/d macrophages and after inhibition of the β-, or γ-secretase, especially after additional immunological activation with lipopolysaccharide (LPS). Secretion of IL-10 was increased after pharmacological inhibition of APP processing when the macrophages were not immunologically activated but was decreased during LPS-induced inflammation in APPk/d macrophages. No changes of the phagocytotic activity were observed. We conclude that macrophage APP and Aβ peptides support the initiation of an immune response and are involved in the regulation of TNFα, IL-6, and IL-10 secretion by human monocyte-derived macrophages.
CRIS-Team Scopus Importer:2020-09-25
Keywords: Abeta; Alzheimer; amyloid; amyloid precursor protein; BACE; cytokine; immune system; secretase

Plasma concentrations of the amyloid-? peptides in young volunteers: the influence of the APOE genotype - Zimmermann, Rüdiger; Huber, Ellen; Schamber, Christine; Lelental, Natalia; Mroczko, Barbara; Brandner, Sebastian; Maler, Juan Manuel; Oberstein, Timo; Szmitkowski, Maciej; Rauh, Manfred; Kornhuber, Johannes; Lewczuk, Piotr (Journal of Alzheimer's Disease, 2014)
Changes in the concentrations of amyloid-? (A?) in the body fluids are the earliest alterations observed in Alzheimer's disease (AD), however, there is a lack of data about how early these alterations occur, before the onset of the clinical symptoms. APOE genotype is the most recognized genetic risk/protective factor of AD, meaning that a group of non-demented persons carrying ?4 allele is enriched in the subjects who will develop AD, compared to the group of non-carriers. Therefore, we studied the plasma concentrations of A? peptides (A?1-42, A?1-40, A?x-42, and A?x-40), and the APOE genotype in 173 young volunteers (average age, 28 ± 7.6 years) without memory deficits, in order to see whether the non-demented group of subjects at risk already characterize with A? changes three-to-four decades before the age at which dementia usually occurs. We did not find statistically significant differences among the groups of ?4 carriers, ?3 homozygotes, and ?2 carriers. We conclude that the APOE genotype does not influence the metabolism of the A? peptides in young persons without memory deficits.
EVALuna2:18883

Pulsed Arterial Spin Labeling and Segmented Brain Volumetry in the Diagnostic Evaluation of Frontotemporal Dementia, Alzheimer’s Disease and Mild Cognitive Impairment - Marterstock, Dominique; Knott, Michael; Lang, Stefan; Oberstein, Timo; Kornhuber, Johannes; Dörfler, Arnd; Schmidt, Manuel; Hölter, Philip (Tomography, 2022)
Background: Previous studies suggest that brain atrophy can not only be defined by its morphological extent, but also by the cerebral blood flow (CBF) within a certain area of the brain, including white and gray matter. The aim of this study is to investigate known atrophy patterns in different forms of dementia and to compare segmented brain volumetrics and pulsed arterial spin labeling (pASL) data to explore the correlation between brain maps with atrophy and this non-contrast-enhanced brain-perfusion method. Methods: Our study comprised 17 patients with diagnosed cognitive impairment (five Alzheimer’s disease = AD, five frontotemporal dementia = FTD, seven mild cognitive impairment = MCI) and 19 healthy control subjects (CO). All patients and controls underwent 4D-pASL brain-perfusion MR imaging and T1w MPRAGE. The data were assessed regarding relative brain volume on the basis of 286 brain regions, and absolute and relative cerebral blood flow (CBF/rCBF) were derived from pASL data in the corresponding brain regions. Mini-Mental State Examination (MMSE) was performed to assess cognitive functions. Results: FTD patients demonstrated significant brain atrophy in 43 brain regions compared to CO. Patients with MCI showed significant brain atrophy in 18 brain regions compared to CO, whereas AD patients only showed six brain regions with significant brain atrophy compared to CO. There was good correlation of brain atrophy and pASL perfusion data in five brain regions of patients with diagnosed FTD, especially in the superior temporal gyrus (r = 0.900, p = 0.037), the inferior frontal white matter (pars orbitalis; r = 0.968, p = 0.007) and the thalami (r = 0.810, p = 0.015). Patients with MCI demonstrated a correlation in one brain region (left inferior fronto-occipital fasciculus; r = 0.786, p = 0.036), whereas patients with diagnosed AD revealed no correlation. Conclusions: pASL can detect affected brain regions in cognitive impairment and corresponds with brain atrophy, especially for patients suffering from FTD and MCI. However, there was no correlation of perfusion alterations and brain atrophy in AD. pASL perfusion might thus represent a promising tool for noninvasive brain-perfusion evaluation in specific dementia subtypes as a complimentary imaging-based bio marker in addition to brain volumetry.
CRIS-Team Scopus Importer:2022-02-11
Keywords: Alzheimer’s disease; Brain volumetry; Dementia; Frontotemporal dementia; Mild cognitive impairment; Pulsed arterial spin labeling

Reconceptualization of the Erlangen Score for the Assessment of Dementia Risk: The ERlangen Score - Utz, Janine; Olm, Pauline; Jablonowski, Johannes; Siegmann, Eva-Maria; Spitzer, Philipp; Lewczuk, Piotr; Kornhuber, Johannes; Maler, Juan Manuel; Oberstein, Timo (Journal of Alzheimer's Disease, 2023)
BACKGROUND: The established Erlangen Score (ES) for the interpretation of cerebrospinal fluid (CSF) biomarkers in the diagnostics of Alzheimer's disease (AD) uses markers of amyloidopathy and tauopathy, equally weighted to form an easy-interpretable ordinal scale. However, these biomarkers are not equally predictive for AD. OBJECTIVE: The higher weighting of the Aβ42/Aβ40 ratio, as a reconceptualized ERlangen Score (ERS), was tested for advantages in diagnostic performance. METHODS: Non-demented subjects (N = 154) with a mean follow up of 5 years were assigned to a group ranging from 0 to 4 in ES or ERS. Psychometric trajectories and dementia risk were assessed. RESULTS: The distribution of subjects between ES and ERS among the groups differed considerably, as grouping allocated 32 subjects to ES group 2, but only 2 to ERS group 2. The discriminative accuracy between the ES (AUC 73.2%, 95% CI [64.2, 82.2]) and ERS (AUC 72.0%, 95% CI [63.1, 81.0]) for dementia risk showed no significant difference. Without consideration of the Aβ42/Aβ40 ratio in ES grouping, the optimal cut-off of the ES shifted to ≥2. CONCLUSIONS: The ERS showed advantages over the ES in test interpretation with comparable overall test performance, as fewer cases were allocated to the intermediate risk group. The established cut-off of ≥2 can be maintained for the ERS, whereas it must be adjusted for the ES when determining the Aβ42/Aβ40 ratio.
CRIS-Team Scopus Importer:2023-11-10
Keywords: Alzheimer’s disease; dementia risk; Erlangen Score; longitudinal study; neuropsychological trajectories

Spot quantification in two dimensional gel electrophoresis image analysis: comparison of different approaches and presentation of a novel compound fitting algorithm - Brauner, Jan M.; Groemer, Teja W.; Stroebel, Armin; Grosse-Holz, Simon; Oberstein, Timo; Wiltfang, Jens; Kornhuber, Johannes; Maler, Juan Manuel (BMC Bioinformatics, 2014)
Various computer-based methods exist for the detection and quantification of protein spots in two dimensional gel electrophoresis images. Area-based methods are commonly used for spot quantification: an area is assigned to each spot and the sum of the pixel intensities in that area, the so-called volume, is used a measure for spot signal. Other methods use the optical density, i.e. the intensity of the most intense pixel of a spot, or calculate the volume from the parameters of a fitted function.In this study we compare the performance of different spot quantification methods using synthetic and real data. We propose a ready-to-use algorithm for spot detection and quantification that uses fitting of two dimensional Gaussian function curves for the extraction of data from two dimensional gel electrophoresis (2-DE) images. The algorithm implements fitting using logical compounds and is computationally efficient. The applicability of the compound fitting algorithm was evaluated for various simulated data and compared with other quantification approaches. We provide evidence that even if an incorrect bell-shaped function is used, the fitting method is superior to other approaches, especially when spots overlap. Finally, we validated the method with experimental data of urea-based 2-DE of A? peptides andre-analyzed published data sets. Our methods showed higher precision and accuracy than other approaches when applied to exposure time series and standard gels.Compound fitting as a quantification method for 2-DE spots shows several advantages over other approaches and could be combined with various spot detection methods.The algorithm was scripted in MATLAB (Mathworks) and is available as a supplemental file.
EVALuna2:23627

The applause sign in frontotemporal lobar degeneration and related conditions - Schoenecker, Sonja; Hell, Franz; Boetzel, Kai; Wlasich, Elisabeth; Ackl, Nibal; Suessmair, Christine; Otto, Markus; Anderl-Straub, Sarah; Ludolph, Albert; Kassubek, Jan; Huppertz, Hans-Juergen; Diehl-Schmid, Janine; et al. (Journal of Neurology, 2019)
The applause sign, i.e., the inability to execute the same amount of claps as performed by the examiner, was originally reported as a sign specific for progressive supranuclear palsy (PSP). Recent research, however, has provided evidence for the occurrence of the applause sign in various conditions. The aim of this study was to determine the prevalence of the applause sign and correlate its presence with neuropsychological and MRI volumetry findings in frontotemporal lobar degeneration and related conditions. The applause sign was elicited with the three clap test (TCT), with a higher score indicating poorer performance. Data were recorded from 272 patients from the cohort of the German consortium for frontotemporal lobar degeneration (FTLDc): 111 with behavioral variant frontotemporal dementia (bvFTD), 98 with primary progressive aphasia (PPA), 30 with progressive supranuclear palsy Richardson's syndrome, 17 with corticobasal syndrome (CBS) and 16 with amyotrophic lateral sclerosis with frontotemporal dementia (ALS/FTD). For comparison, 29 healthy elderly control subjects (HC) were enrolled in the study. All subjects underwent detailed language and neuropsychological assessment. In a subset of 156 subjects, atlas-based volumetry was performed. The applause sign occurred in all patient groups (40% in PSP, 29.5% in CBS, 25% in ALS/FTD, 13.3% in PPA and 9.0% in bvFTD) but not in healthy controls. The prevalence was highest in PSP patients. It was significantly more common in PSP as compared to bvFTD, PPA and HC. The comparison between the other groups failed to show a significant difference regarding the occurrence of the applause sign. The applause sign was highly correlated to a number of neuropsychological findings, especially to measures of executive, visuospatial, and language function as well as measures of disease severity. TCT scores showed an inverse correlation with the volume of the ventral diencephalon and the pallidum. Furthermore the volume of the ventral diencephalon and pallidum were significantly smaller in patients displaying the applause sign. Our study confirms the occurrence of the applause sign in bvFTD, PSP and CBS and adds PPA and ALS/FTD to these conditions. Although still suggestive of PSP, clinically it must be interpreted with caution. From the correlation with various cognitive measures we suggest the applause sign to be indicative of disease severity. Furthermore we suggest that the applause sign represents dysfunction of the pallidum and the subthalamic nucleus, structures which are known to play important roles in response inhibition.
CRIS-Team WoS Importer:2019-02-21

The Cost of Early Diagnosis of Cognitive Decline in German Memory Clinics - Onurl, Oezguer A.; Wolff-Menzler, Claus; Von Arnim, Christine A. F.; Jessen, Frank; Fink, Gereon R.; Wiltfang, Jens; Laske, Christoph; Schneider, Anja; Levinl, Johannes; Oberstein, Timo; Kornhuber, Johannes; Oberhauser, Felix; et al. (Fortschritte der Neurologie - Psychiatrie, 2022)
Dementias are expensive diseases: the net annual cost in European healthcare is about euro 28.000 per case with a strong stage dependency, of which medical care accounts for about 19%. Diagnostic costs, on the other hand, account for only a small proportion of the total costs. With changes in the guidelines, biomarker tests are becoming increasingly important. At present, the concrete economic impact of biomarker-based diagnosis is largely unknown. To determine the actual costs of diagnostic procedures based on guidelines, we conducted a survey among the members of the German Memory Clinic Network (DNG). From 15 expert centres, the staff engagement time for all procedures was collected. Based on the individual engagement times of the different professions, the total of personnel costs for diagnostics was calculated using current gross personnel costs. The total sum of diagnostic costs (personnel plus procedures) was calculated for three different scenarios e. g. euro 633,97 for diagnostics without biomarkers, euro 1.214,90 for diagnostics with CSF biomarkers and euro 4.740,58 euro for diagnostics with FDG- plus Amyloid-PET. In addition, the actual diagnostic costs of the current practice in expert memory clinics were estimated, taking into account personnel costs, costs for the different procedures and the frequency of their use across all patients. This results in total average costs of euro 1.394,43 per case as the mean across all centres (personnel costs euro 351,72, costs for diagnostic procedures euro 1.042,71). The results show that state-of-the-art diagnosis of dementia and pre-dementia states, such as mild cognitive impairment (MCI) requires financial resources, which are currently not fully reimbursed in Germany. The need for a biomarker-based etiological diagnosis of dementia and pre-dementia states will increase, due to availability of disease-modifying treatments. Therefore, the current gap of reimbursement must be filled by new models of compensation.
CRIS-Team WoS Importer:2022-07-29

The German Dementia Registry (DEMREG): study protocol of a biomarker-based national registry for cognitive impairment and dementia - Reetz, Kathrin; Costa, Ana Sofia; Michels, Jennifer; Albrecht, Milena; Moschko, Pia; Pahl, Jennifer; Häger, Alexa; Schuckelt, Rainer; Röhrig, Rainer; Wienströer, Jan; Flöel, Agnes; Düzel, Emrah; et al. (Neurological Research and Practice, 2025)
Introduction: The German Dementia Registry (DEMREG) is a large-scale national prospective biomarker-based study for cognitive impairment and dementia, providing an integrated clinical research platform for research studies. Methods: The DEMREG study longitudinally collects demographic, clinical, genetic, biological, and imaging data, along with risk factors and treatment information from real-world settings. Comprehensive clinical assessments are conducted yearly. This extensive resource enables researchers to investigate current diagnostic and treatment practices and explore the complex relationships between risk factors and outcomes. The registry is now active across 22 sites in Germany, all members of the the German Memory Clinic Network (DNG), with more than 500 patients recruited to date, and is expected to include up to 1.000 patients annually. Perspective: The DEMREG study represents a large nationally harmonized cohort of detailed real-world clinical and biological data from patients with cognitive impairment and dementia, enabling insights into long-term dynamics and treatment responses. This infrastructure has the potential to foster collaborative research and roll out healthcare innovations across different settings in Germany. In this context, a substudy will soon be conducted to evaluate long-term safety and efficacy measures of the new monoclonal antibodies targeting amyloid plaques in a clinical setting. Trial registration: The protocol is registered at German Clinical Trials Register (DRKS00027547), Date of Registration: 01.04.2022.
CRIS-Team Scopus Importer:2025-11-21
Keywords: Biomarkers; Dementia; Mild cognitive impairment; Natural history; Neurodegeneration; Registry; Treatment

The Role of Cathepsin B in the Degradation of Aβ and in the Production of Aβ Peptides Starting With Ala2 in Cultured Astrocytes - Oberstein, Timo; Utz, Janine; Spitzer, Philipp; Klafki, Hans Wolfgang; Wiltfang, Jens; Lewczuk, Piotr; Kornhuber, Johannes; Maler, Juan Manuel (Frontiers in Molecular Neuroscience, 2021)
Astrocytes may not only be involved in the clearance of Amyloid beta peptides (Aβ) in Alzheimer's disease (AD), but appear to produce N-terminally truncated Aβ (Aβn−x) independently of BACE1, which generates the N-Terminus of Aβ starting with Asp1 (Aβ1−x). A candidate protease for the generation of Aβn−x is cathepsin B (CatB), especially since CatB has also been reported to degrade Aβ, which could explain the opposite roles of astrocytes in AD. In this study, we investigated the influence of CatB inhibitors and the deletion of the gene encoding CatB (CTSB) using CRISPR/Cas9 technology on Aβ2−x and Aβ1−x levels in cell culture supernatants by one- and two-dimensional Urea-SDS-PAGE followed by immunoblot. While the cell-permeant inhibitors E64d and CA-074 Me did not significantly affect the Aβ1−x levels in supernatants of cultured chicken and human astrocytes, they did reduce the Aβ2−x levels. In the glioma-derived cell line H4, the Aβ2−x levels were likewise decreased in supernatants by treatment with the more specific, but cell-impermeant CatB-inhibitor CA-074, by CA-074 Me treatment, and by CTSB gene deletion. Additionally, a more than 2-fold increase in secreted Aβ1−x was observed under the latter two conditions. The CA-074 Me-mediated increase of Aβ1−x, but not the decrease of Aβ2−x, was influenced by concomitant treatment with the vacuolar H+-ATPase inhibitor Bafilomycin A1. This indicated that non-lysosomal CatB mediated the production of Aβ2−x in astrocytes, while the degradation of Aβ1−x seemed to be dependent on lysosomal CatB in H4 cells, but not in primary astrocytes. These findings highlight the importance of considering organelle targeting in drug development to promote Aβ degradation.
CRIS-Team Scopus Importer:2021-02-05
Keywords: Alzheimer's disease; amyloid beta; astrocytes; cathepsin B; lysosomal; N-terminus